Synergy Repetition Training versus Task Repetition Training in Acquiring New Skill - Patel, Vrajeshri; Craig, Jamie; Schumacher, Michelle; Burns, Martin K.; Florescu, Ionut; Vinjamuri, Ramana (Frontiers in Bioengineering and Biotechnology, 2017)
Traditionally, repetitive practice of a task is used to learn a new skill, exhibiting as immediately improved performance. Research suggests, however, that a more varied training protocol, may allow for better transference of the skill to a new, but related task. In synergy-based motor control theory, fundamental motor skills, such as hand grasping, are represented with a synergy subspace that captures essential motor patterns. In this study, we propose that motor skill learning through synergy-based mechanisms may provide advantages over traditional repetition learning. A new task was designed to highlight the range of motion and dexterity of the human hand. Two separate training strategies were tested in healthy subjects: repetition training and synergy training, versus a control. All three groups showed improvements when retested on the same task. When tested on a new task, only the synergy group showed significant improvements in accuracy (9.27% increase) compared to the repetition (3.24% decline) and control (3.22% decline) groups. Average completion time was also shortest for the synergy group in the new task. A kinematic analysis revealed that the timing benefits may have resulted from the initial feed-forward portion of the task, while accuracy improvements may have derived from general improved coordination amongst the four involved fingers. These results support the use of synergy-based motor training in healthy individuals, but can potentially benefit individuals undergoing hand-based rehabilitative therapy.